Empowering Islamic Educational Institutions through Strengthening Operational Licensing and Management of TPQ/Madin - Elfany Hunafa Salsabilla (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This community service program addressed the challenges faced by informal Islamic educational institutions (TPQ/Madin) in Senggowar Village, particularly regarding operational licensing and institutional management. Employing the Asset-Based Community Development (ABCD) approach, the initiative shifted the paradigm from a deficit-based to a strengths-based model. The methodology followed the ABCD cycle: Discovery (mapping institutional assets and challenges), Dream (facilitating a collective vision for formalized and well-managed institutions), Design (cocreating action plans for licensing and management systems), and Destiny (implementing assistance and capacity building). The intervention resulted in three TPQ/Madin institutions initiating the formal licensing process with the Ministry of Religious Affairs and the adoption of simple, standardized management tools for student administration and financial recording. Beyond these tangible outputs, the program fostered significant institutional capacity building, enhanced collaboration among institution leaders, and increased community trust. The project demonstrates that the ABCD framework is an effective strategy for strengthening the foundational governance of community-based educational institutions, leading to greater sustainability, legitimacy, and quality of service in Islamic education at the grassroots level